TEACHERS'S LIFE SATISFACTION IN PALOPO AND TORAJA: A DESCRIPTIVE STUDY - Yusak Novanto; Marthen Pali (Universitas Negeri Malang, 2019)
Life satisfaction plays an important role in the quality of life and performance of a human in any profession, including teachers. The teacher is a professional educator with the main task of educating, teaching, guiding, directing, training, and evaluating students in elementary and middle schools. Life satisfaction refers to an individual’s overall judgment or global evaluation about his or her life condition. This study is a quantitative descriptive survey study that aims to analyze and describe the relationship between demographic factors with school teachers’ life satisfaction at Palopo and Toraja Region in South Sulawesi. This research using SWLS (Satisfaction with Life Scale) with 111 respondents who came from several schools in Palopo and Toraja region. Result of this research found that most of the teachers (67,6%) were satisfied with their lives, and the rest (32,4 %) are not satisfied with their lives. Based on the cross-tabulation analysis and non-parametric correlation, its proven that several demographic factors, namely gender, employment status, ethnic groups, length of services, income perception, and salary comparison perception have a significant correlation with teachers’ life satisfaction. In particular, with ordinal regression analysis, we found that educational status, income perception, and salary comparison perception has influence teachers' life satisfaction. Government and Private Educational Foundation should do effort to increase teacher’s income and have a career development plan for teachers to maintain their subjective wellbeing level. Keywords: demographic factors, life satisfaction, Palopo and Toraja, teacherDOI: http://dx.doi.org/10.17977/um023v8i22019p207